Pengembangan E-LKPD Berbasis Problem Based Learning Terintegrasi Keterampilan 4C untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada Mata Pelajaran Ekonomi - Ina Sukmawati; Muhammad Abdul Ghofur (Jurnal Paedagogy, 2023)
This study aims to develop an E-LKPD based on Problem-Based Learning integrated 4C skills to improve students' critical thinking ability in economics subjects. This research method used research and development (R&D) with the ADDIE model. The subjects of this study were students of class XI IPS 1 at SMA Negeri 1 Babat. The research instruments used were interview guidelines, questionnaires, and pre-test and post-test sheets. Meanwhile, the data analysis technique used instrument test analysis on validity, reliability, difficulty, and discrimination. The results of the study showed that E-LKPD could improve students' critical thinking skills through 4C skill-based learning features with n-gain, a score of 0.48, which is in the moderate category. These results were supported by students' positive responses to using the E-LKPD. Thus, the development of the E-LKPD is effective in improving students' critical thinking ability.